Release me. 2 [compact disc] - Streisand, Barbra; Nelson, Willie, 1933-; Kermit, the Frog; Gibb, Barry, 1946- (Columbia/Legacy, 2021)
The follow-up to her acclaimed 2012 album, Release Me, this new collection contains previously unreleased tracks from Barbra's vault, including duets with Willie Nelson and Kermit the Frog.